Informing Digital Futures Strategies for Citizen Engagement - Damodaran, Leela; Olphert, Wendy (Computer Supported Cooperative Work, 2006)
In the present digital revolution we often seem trapped in a Kafkaesque world of technological advances, some desired, some disliked or even feared, which we cannot influence but must accept. This book discusses the urgent need to redress this situation. The authors argue that technologies succeed or fail according to their relevance and value to people, who need to be actively engaged in order to create shared visions and influence their implementation. Strategies for citizen engagement and empowerment will enable citizens to influence and shape desirable digital futures. The book reviews the currently accepted ways of thinking about the design of systems and the reasons why these methods are no longer adequate. From an academically rigorous analysis of case histories across a wide variety of sectors, knowledge and best practice are captured in a rich, descriptive model of the contributions of citizen engagement to the design process. Finally, it provides specific practical guidance, based on sound academic research, for policy makers, administrators and ICT professionals on the strategies, methodologies, tools and techniques needed to change design practice.